Textile language: an occult heritage by the way of the lord of Chimu’s cloth - Gutiérrez, Cristina (2017)
From the semiotic analysis of a Chimu ceremonial costume, one of the most complete textile expressions of our culture, we approach the discourse within it breaking up a series of meanings related to the ancient Peruvian ́s thinking and their cosmology that are in fact still very much alive in the customs and habits of the Trujillo region modern day inhabitants.